2004
DOI: 10.1152/ajpheart.01019.2003
|View full text |Cite
|
Sign up to set email alerts
|

Excessive ATP hydrolysis in ischemic myocardium by mitochondrial F1F0-ATPase: effect of selective pharmacological inhibition of mitochondrial ATPase hydrolase activity

Abstract: Mitochondrial F(1)F(0)-ATPase normally synthesizes ATP in the heart, but under ischemic conditions this enzyme paradoxically causes ATP hydrolysis. Nonselective inhibitors of this enzyme (aurovertin, oligomycin) inhibit ATP synthesis in normal tissue but also inhibit ATP hydrolysis in ischemic myocardium. We characterized the profile of aurovertin and oligomycin in ischemic and nonischemic rat myocardium and compared this with the profile of BMS-199264, which only inhibits F(1)F(0)-ATP hydrolase activity. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 30 publications
4
86
0
Order By: Relevance
“…Moreover, Grover et al (12) reported that excessive ATP hydrolysis by F 1 F O -ATPase contributed to the decline in cardiac energy reserve during ischemia and that selective inhibition of ATP hydrolase activity could protect ischemic myocardium in male rats. Taken together, it seems likely that the pre-ischemic treatment of male rats with oligomycin would prevent ischemiainduced renal ATP depletion through inhibition of ATP hydrolysis by F 1 F O -ATPase and exerts a protective effect on ischemia/reperfusion-induced renal damage.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Grover et al (12) reported that excessive ATP hydrolysis by F 1 F O -ATPase contributed to the decline in cardiac energy reserve during ischemia and that selective inhibition of ATP hydrolase activity could protect ischemic myocardium in male rats. Taken together, it seems likely that the pre-ischemic treatment of male rats with oligomycin would prevent ischemiainduced renal ATP depletion through inhibition of ATP hydrolysis by F 1 F O -ATPase and exerts a protective effect on ischemia/reperfusion-induced renal damage.…”
Section: Figmentioning
confidence: 99%
“…In addition, proteomic analysis showed that the b subunit of F 1 F O -ATPase was significantly up-regulated 2 h after the reperfusion in ischemia/reperfusion-treated male rat kidneys, but not in female kidneys (10). F 1 F O -ATPase has been reported to play a role in the pathophysiology of myocardial ischemia/reperfusion injury in isolated male rat hearts (11,12). Taken together, there is a possibility that F 1 F O -ATPase is a key component of the sex difference in ischemic acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…104 In the ischaemic myocardium it is demonstrated that ATP levels at reperfusion are replenished faster and necrosis is reduced when using an ATP-hydrolase inhibitor. 105 In glucose-deprived rat neonatal cardiac myocytes exposed to hypoxia, a positive correlation between myocyte ATP concentration and the percentage of apoptotic cells is described. By increasing the glucose concentration, apoptosis progressively replaces necrotic cells, 106 underlining the importance of substrate availability in the cell death decisionmaking process.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…During ischemia, the proton-translocating F0F1-ATP synthase, which normally produces ATP, becomes an F0F1-ATPase and consumes ATP in order to pump protons from the matrix to the intermembrane space and maintain the mitochondrial membrane potential. [39], [40] The mitochondria therefore become a site of ATP consumption produced by anaerobic glycolysis.…”
Section: Disturbance Of Atp Synthesismentioning
confidence: 99%